The genus Scatopsciara Edwards (Diptera, Sciaridae) in New Caledonia, with the description of four new species - Vilkamaa, Pekka; Hippa, Heikki; Mohrig, Werner (Zootaxa, 2012)
The following species of the genus Scatopsciara Edwards, 1927 are recognized from New Caledonia, all newly described: Scatopsciara (Xenopygina) exigua sp. n., Scatopsciara (s.str.) spiculata sp. n., S. (s. str.) tenuistylata sp. n. and S. (s. str.) vicina sp. n. A key to the species is given.